Blind Box Preferences Under Uncertainty: A Positioning-Schema-Value Model with Self-Determination Motivation - Ummu Savira Maulida Akhmad (CV. Doki Course and Training, 2026)
This conceptual article develops an integrative model to explain the formation of consumer preferences for blind boxes in conditions of uncertainty through the linkage of brand strategy, consumer cognitive structure, and motivational orientation. The purpose of this study is to formulate the process mechanism whereby brand positioning shapes brand schema, schema helps consumers interpret uncertainty, and the results of that interpretation accumulate into perceived value, which then drives preference. The method used is narrative conceptual synthesis to integrate literature on positioning and brand meaning, schema-based information processing, perceived value theory, and Self-Determination Theory. The synthesis results in a Positioning–Schema–Value model with four testable propositions: (1) brand positioning positively influences the formation of brand schema, (2) brand schema positively influences perceived value of blind boxes, (3) perceived value positively influences consumer preferences, and (4) intrinsic and extrinsic motivation moderate the relationship between perceived value and preferences. This model explains why uncertainty can be interpreted as a source of emotional and symbolic value, and why consumers with similar levels of perceived value can show different strengths of preference. In conclusion, managing blind box preferences requires consistent positioning that aligns with the target schema and motivational apel settings to increase value without reinforcing harmful impulsivity. This framework provides a theoretical basis for further empirical testing through survey-based SEM or experiments.